CRITICISM ABOUT ADOLESCENT CONSUMPTIVE BEHAVIOUR: RECEPTION ANALYSIS ON “SPINE BREAKER” LYRICS BY BTS - Paundra, Annisa Mutiara; Kusuma, Rina Sari (Jurnal Media dan Komunikasi Indonesia, 2024)
Consumptive behavior is an act of excessive prioritization of desire or wants over need or necessity and it has no predominance scale, this is rooted in the fact that adolescents are the most consumptive age. “Spine Breaker” by BTS highlights the rampant consumerism by adolescents due to peer pressure and how adolescents tend to beg their parents for necessities that they can’t afford. This study aims to examine the discernment of ARMY, the fandom name for BTS’ fans, towards the message about criticism regarding adolescent consumptive behavior that is conveyed through the lyrics of “Spine Breaker” by BTS using the purposive sampling technique. Therefore, there are six respondents. This research used a qualitative approach. The respondents who are also part of the fandom are classified into three different groups based on their economic status and later the Focus Group Discussion (FGD) is used for data collection purposes. Thus the six respondents in this study have been divided into three groups based on their economic status, and later the result of this research is the division of respondents into two audience positions; the dominant hegemony and the negotiating position in relation to Stuart Hall’s reception theory.